Marginalized community effort to improve environmental quality of poor settlement along riverbank - Paulus Bawole; Haryati Sutanto (Universitas Gadjah Mada, 2023)
Currently, many people live in urban areas and more than 30% of them live in slums or squatter settlements. Urbanization is one of the most transformative trends occurring worldwide, especially in developing countries like Indonesia. At present, more than half of the total population in Indonesia lives in urban areas. The dominance of the urban population shows the urgency to make the urban environment inclusive, safe, resilient, and sustainable as it is intended to be realized through Goal No. 11 - SDGs 2030. Cities require large spaces and are a major source of wealth and centers of innovation, culture, and politics. The urban area has become the most important arena for people, including low-income communities that live in informal urban spaces that develop spontaneously. This article will share research experiences on the settlements of marginalized communities. With the help of several institutions, the communities are trying to improve the quality of their settlements to become inclusive, safe, resilient, and sustainable. The method used in this research is the descriptive-qualitative method exploring the potential and resources within urban kampong to improve the quality of urban poor settlements. With the discovery of informal urban space patterns and community efforts to improve the quality of their settlements, a sustainable development strategy can be developed to improve urban areas inhabited by low-income people.